Tick-borne encephalitis virus modulates sphingolipid and phospholipid metabolism in infected human neuronal cells - Šimečková, Pavlína; Slavík, Josef; Fořtová, Andrea; Huvarová, Ivana; Králiková, Lucie; Stefanik, Michal; Svoboda, Pavel; Ruzek, Daniel; Machala, Miroslav (Microbes and infection, 2024)
The life cycle of enveloped viruses is closely linked to host-cell lipids. However, changes in lipid metabolism during infections with the tick-borne encephalitis virus (TBEV) have not been described. TBEV is a medically important orthoflavivirus, which is endemic to many parts of Europe and Asia. In the present study, we performed targeted lipidomics with HPLC-MS/MS to evaluate changes in phospholipid and sphingolipid concentrations in TBEV-infected human neuronal SK-N-SH cells. TBEV infections significantly increased phosphatidylcholine, phosphatidylinositol, and phosphatidylserine levels within 48 h post-infection (hpi). Sphingolipids were slightly increased in dihydroceramides within 24 hpi. Later, at 48 hpi, the contents of sphinganine, dihydroceramides, ceramides, glucosylceramides, and ganglioside GD3 were elevated. On the other hand, sphingosine-1-phosphate content was slightly reduced in TBEV-infected cells. Changes in sphingolipid concentrations were accompanied by suppressed expression of a majority of the genes linked to sphingolipid and glycosphingolipid metabolism. Furthermore, we found that a pharmacological inhibitor of sphingolipid synthesis, fenretinide (4-HPR), inhibited TBEV infections in SK-N-SH cells. Taken together, our results suggested that both structural and signaling functions of lipids could be affected during TBEV infections. These changes might be connected to virus propagation and/or host-cell defense.
Keywords: Lipidomics; 4-HPR; Sphingolipids; Fenretinide; buněčné linie; Tandem Mass Spectrometry; fosfolipidy; lidé; Lipid Metabolism; neurony; viry klíšťové encefalitidy; Targeted lipidomics; metabolismus lipidů; sfingolipidy; Cell Line; Encephalitis Viruses, Tick-Borne; Neurons; Tick-borne encephalitis virus; tandemová hmotnostní spektrometrie; lipidomika; Phospholipids; interakce hostitele a patogenu; Host-Pathogen Interactions; Human neuronal cells; Humans